STRATEGY FOR ENHANCING MATHEMATICAL SKILLS THROUGH THE SMART CORNER IN EARLY CHILDHOOD EDUCATION - Ailsa Syahda Firjatullah (Journal of Art and Creativity in Early Childhood Education, 2025)
This study aims to describe the use of the "Smart Corner" (Pojok Cerdas) as a learning strategy to enhance mathematical abilities in children aged 5–6 years at TK IT Nada Ashobah. The research employed a descriptive qualitative method, focusing on naturalistic observation, interviews with teachers, and documentation of learning activities. Data were analyzed through data reduction, data display, and drawing conclusions. The findings reveal that the Smart Corner encourages active participation, exploration, and independent problem-solving in early numeracy skills such as counting, sorting, and recognizing patterns. Teachers play a crucial role in guiding and facilitating meaningful interactions through carefully selected materials and structured learning spaces. The learning environment supports children’s curiosity and builds a foundation for mathematical thinking through play-based experiences. The study concludes that integrating a Smart Corner in early childhood classrooms effectively supports the development of basic mathematical skills and fosters a positive attitude toward learning. These findings suggest that similar strategies could be implemented in other early childhood education settings to promote active and engaging mathematics learning.